Etude la qualité sanitaire du lait cru de vache et du lait pasteurisé au niveau de l'entreprise Giplait de Mostaganem - BENYAMNA, Fatima Zohra (My University, 2021)
Milk is a complete food and can be contaminated with bacteria and cause illness. To mitigate this risk, monitoring the microbiological quality of the latter is important and necessary in order to avoid any public health problems. The purpose of this study is to assess the microbiological quality of raw and pasteurized milk: The microbiological analysis focused on 4 microbial groups: hygiene indicator groups (total aerobic germs, fecal coliforms), and pathogenic groups (Staphylococcus aureus, salmonella). The results of the microbiological analyzes of raw milk are unsatisfactory, therefore it is unacceptable due to a high rate of total aerobic germs (9.105UFC/ml) and fecal coliforms (8.102UFC/ml) in our samples which contradicts the Algerian standard. On the other hand, the results obtained with pasteurized milk are satisfactory, so it is acceptable following the effectiveness of the treatment measures.
Keywords: Raw milk - pasteurized milk - sanitary quality - microbiological analyzes.